2017
DOI: 10.1002/ange.201609708
|View full text |Cite
|
Sign up to set email alerts
|

GXXXG‐Mediated Parallel and Antiparallel Dimerization of Transmembrane Helices and Its Inhibition by Cholesterol: Single‐Pair FRET and 2D IR Studies

Abstract: Small-residue-mediated interhelical packings are ubiquitously found in helical membrane proteins, although their interaction dynamics and lipid dependence remain mostly uncharacterized. We used a single-pair FRET technique to examine the effect of a GXXXG motif on the association of denovo designed (AALALAA) 3 helices in liposomes. Dimerization occurred with sub-second lifetimes, which was abolished by cholesterol. Utilizing the nearly instantaneous time-resolution of 2D IR spectroscopy, parallel and antiparal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“… 6 8 In contrast, our simulation with the GXXXG motif revealed a tightly packed dimer with a small crossing angle ( Figure 4 ), in agreement with the findings of the single-pair FRET experiments. 17 In addition, only a few hydrogen bonds were observed in the GXXXG dimer ( Figure 3 ). This difference in the mechanisms of dimerization by the GXXXG motif is likely caused by the peptide sequences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 6 8 In contrast, our simulation with the GXXXG motif revealed a tightly packed dimer with a small crossing angle ( Figure 4 ), in agreement with the findings of the single-pair FRET experiments. 17 In addition, only a few hydrogen bonds were observed in the GXXXG dimer ( Figure 3 ). This difference in the mechanisms of dimerization by the GXXXG motif is likely caused by the peptide sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In the models of the GXXXG parallel dimers, our simulations showed that introducing cholesterols reduced the interpeptide contacts, which agrees with the results of the single-pair FRET experiments. 17 Because the cholesterols thickened the membrane ( Figure 5 ), the tilt and crossing angles decreased to minimize the hydrophobic mismatch ( Figure 4 ). Tighter packing of the two helices sterically requires a certain crossing angle, and thus a decrease in the crossing angle weakens the peptide–peptide packing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations